User selection protocols in FD PSP EH cooperative network over rayleigh fading channel: outage and intercept probability - Tran Tin, Phu; Tran, Minh; Phan, Van-Duc; Nguyen, Hoang-Nam; Nguyen, Thanh-Long (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
In this paper, we investigate the system performance in term of outage probability (OP) and intercept probability (IP) user selection protocols in full-duplex (FD) power splitting protocol (PSP) energy harvesting (EH) cooperative network over the Rayleigh fading channel. In this network, security and privacy issues are significant due to the possible eavesdropping by surrounding users. In this case, the security performance and reliable performance are represented by outage probability (OP) and intercept probability (IP), respectively. The power-splitting energy harvesting protocol is applied in our analysis. We rigorously derive the closed-form expressions of both OP and IP of the system and study the effect of various parameters. Finally, the Monte Carlo simulation results are also performed to confirm the correctness of all theoretical analysis derived.